THE MACROECONOMIC SURPRISE EFFECTS ON LQ45 STOCK RETURN VOLATILITY - Andika, Tommy; Fahmi, Idqan; Andati, Trias (Universitas Brawijaya, Indonesia, 2019)
Surprise macroeconomic news causes high volatility in stock market return to the stock market becomes riskier. This study aims to analyze the effects of surprise from the announcement of the United States (US) and domestic macroeconomic news on the LQ45 stock returns volatility. There are 25 stocks chosen because consistently in LQ45 during the 2013 - 2018 research period. The Generalized Autoregressive Conditional Heteroscedasticity (GARCH) model is used to analyze the volatility of returns for each stock. The analysis shows that negative surprise from the Bank Indonesia benchmark interest rate, positive surprise from Indonesia's trade balance, positive surprise from Consumer Price Index US, and positive surprise from ISM Manufacturing US have a significant effect in reducing volatility return and making most LQ45 Stocks return more stable and less risky. Other macroeconomic surprises show different directions of influence. Finally, this study also provides recommendations for the investor to choose stocks according to their respective risk profiles. The risk averse investor can invest in PT Astra International Tbk (ASII), PT Lippo Karawaci Tbk (LPKR) and PT AKR Corporindo Tbk (AKRA) which have low volatility during the release of surprise macroeconomic, while the risk taker investor can invest to PT Astra Agro Lestari Tbk (AALI), PT Vale Indonesia Tbk (INCO), and PT. Media Nusantara Citra Tbk (MNCN) which respond to many surprises of macroeconomic news.